Update of survival and cost of metastatic melanoma with new drugs: Estimations from the MelBase cohort. (December 2018) - Kandel, M.; Allayous, C.; Dalle, S.; Mortier, L.; Dalac, S.; Dutriaux, C.; Leccia, M.T.; Guillot, B.; Saiag, P.; Lacour, J.P.; Legoupil, D.; Lesimple, T.; et al.
Abstract: Purpose: Since 2011, significant progress was observed in metastatic melanoma (MM), with the commercialisation of seven immunotherapies or targeted therapies, which showed significant improvement in survival. In France, in 2004, the cost of MM was estimated at €1634 per patient; this cost has not been re-estimated since. This study provided an update on survival and cost in real-life clinical practice. Methods: Clinical and economic data (treatments, hospitalisations, radiotherapy sessions, visits, imaging and biological exams) were extracted from the prospective MelBase cohort, collecting individual data in 955 patients in 26 hospitals, from diagnosis of metastatic disease until death. Survival was estimated by the Kaplan-Meier method. Costs were calculated from the health insurance perspective using French tariffs. For live patients, survival and costs were extrapolated using a multistate model, describing the 5-year course of the disease according to patient prognostic factors and number of treatment lines. Results: Since the availability of new drugs, the mean survival time of MM patients has increased to 23.6 months (95% confidence interval [CI] :21.2;26.6), with 58% of patients receiving a second line of treatment. Mean management costs increased to €269, 682 (95% CI:244, 196;304, 916) per patient. Drugs accounted for 80% of the total cost. Conclusion: This study is the first that evaluated the impact of immunotherapies and targeted therapies both on survival and cost in real-life conditions. Alongside the introduction of breakthrough therapies in the first and subsequent lines, MM has been associated with a significant increase in survival but also in costs, raising the question of financial sustainability. Highlights: This study updates the survival and cost of advanced melanoma since the arrival of targeted therapies and immunotherapies. Costs were calculated using individual data prospectively collected from the MelBase cohort in real-life conditions. Mean survival time of patients with MM was estimated at 23.6 months, for a mean cost estimated at €269, 682 per patient.